Outcomes of a modified approach to transcatheter closure of perimembranous ventricular septal defects. Issue 1 (21st February 2013) - Landman, Geri; Kipps, Alaina; Moore, Phillip; Teitel, David; Meadows, Jeffery
<x xml:space="preserve">Abstract</x> Objectives To describe the immediate and midterm results of a modified method for transcatheter closure of perimembranous ventricular septal defects (pmVSDs). Background Transcatheter closure of pmVSDs has been associated with development of heart block due to impingement on the ventricular conduction system. Ventricular septal aneurysms (VSAs) are common; the VSA tissue can serve as a target for the device without necessitating direct contact with the conduction system. Methods Between 2004 and 2011, 15 patients underwent transcatheter closure of a pmVSD utilizing a device implanted into a VSA. Catheterization reports were examined in addition to pre‐closure, post‐closure, and current clinical, ECG, and echocardiographic data. Results The median age was 20 years (4–61 years), and the most common indication for closure was increasing LV dilation. Four different Amplatzer devices were utilized. Following device implantation there was a decrease in Qp:Qs (1.7–1.1) and in RV:LV pressure ratio (0.36–0.31). There were no deaths, no device embolizations, and no new heart block or PR interval prolongation. Three patients developed a new right bundle branch block (RBBB). The median follow‐up time was 1.5 years (4 months to 7.1 years). Two patients required further procedures for important residual shunting. Six continued to have a "trivial/small" residual leak, but only one had any degree (mild) of residual LV dilation. None of the complications were significantly associated with age or weight at the time of procedure, original size of the VSD, or size or type of the device used. Conclusion Transcatheter closure of pmVSD with placement of the device into the VSA is safe and effective, and may result in fewer instances of atrioventricular block and valve abnormalities than have been reported with alternative methods of pmVSD device closure. Persistent VSDs and new RBBBs remain an important issue. © 2013 Wiley Periodicals, Inc.